Anti-CD3 antibody induces long-term remission of overt autoimmunity in nonobese diabetic mice. - Chatenoud, L (1994)
Anti-CD3 monoclonal antibodies suppress immune responses by transient T-cell depletion and antigenic modulation of the CD3/T-cell receptor complex. Anti-CD3 treatment of adult nonobese diabetic (NOD) mice, a spontaneous model of T-cell-mediated autoimmune insulin-dependent diabetes mellitus, significantly inhibits the autoimmune process. Short-term low-dose anti-CD3 treatment (5 micrograms/day i.v. for 5 consecutive days) prevented the occurrence of an accelerated form of the disease induced by cyclophosphamide. More unexpectedly, when applied to adult NOD females within 7 days of the onset of full-blown diabetes, the same anti-CD3 regimen induced a complete remission of overt disease (i.e., a return to permanent normoglycemia) in 64-80% of mice. This remission was durable (> 4 months) and was not associated with the disappearance of insulitis (mononuclear cell infiltration of the islets). The immunosuppression was apparently specific for beta-cell-associated antigens, since mice showing anti-CD3-induced remission rejected histoincompatible skin grafts normally, whereas they did not destroy syngeneic islet grafts, unlike control untreated overtly diabetic NOD females. These results open major therapeutic perspectives. They strongly suggest that self-tolerance can be restored in adult mice once autoimmunity is fully established and confirm that this effect can be obtained by transient targeting of the CD3/T-cell receptor without massive T-cell debulking.